The selection of elite athletes from an early age: reflection from the perspective of complex systems/La selección de atletas élite desde edad temprana: reflexión desde la perspectiva de los sistemas complejos - Juan Manuel García Manso; Teresa Valverde Esteve; Lázaro de la Paz Arencibia; María José Martínez Patiño (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
Introduction: In this study, the suitability of selecting elite athletes from an early age was examined. Objective: The objective of this study was to verify if the behavior identified in previous research also occurs among the world's best athletes of all time who compete in the 100-meter race. Materials and methods: For this, and based on an analysis of the official classifications of all times for men and women of the International Association of Athletics Federations in the referred test , samples were used in absolute category (Top-1,000 up to the 12/31/2018) and sub -20 category (Top - 100 until 12/31/2003); power laws and other strategies typical of complex systems will be applied to analyze the data . Results: The results show how, all too often, the best male and female runners in the world in the under-20 category do not evolve positively during the rest of their sports career. improving their records in the higher categories. Only 51 men out of the top 100 U-20 runners of all time managed to improve their times once they reached the senior category, and the improvements did not always show statistically significant progressions. Consequently, an excessive investment in human and material resources to identify individuals with high athletic abilities is not always the best strategy. Conclusions: level sport at an early age can be a methodological error that should be avoided when building the sports reserves of a country or sports federation.